Contribution Of Hand Reaction Speed And Feet Movement Speed With Table Tennis Playing Skills - Sahabuddin; Hakim, Hikmad; Muslim, Muslim (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2022)
Table tennis is a very unique type of small ball game. This is because table tennis uses a small ball made of celluloid, lightweight, and uses a bat to hit. This game is played on a table bounded by a net at the center of the table. The purpose of this study was to determine the contribution of hand reaction speed and footwork speed to playing tennis skills. This research belongs to the type of descriptive correlational research using a population of all male students state high school 1Marioriawa Soppeng Regency with a total sample of 40 people selected by random sampling. The data analysis technique used is the correlation analysis technique using the SPSS version 22.00 system at a significant level of 95% or 0.05. Starting from the results of data analysis, this study concludes that: (1) Hand reaction speed has a contribution to playing tennis skills by 61.6%; (2) Footwork speed has a contribution to the skills of playing tennis by 72.4%; and (3) Hand reaction speed and footwork speed have a contribution to the skill of playing tennis by 73.9%.